Effects of Mentoring in the Utilization and Improvisation of Biology Learning Resources on the Performance of Senior Secondary School Students in South West Nigeria - Olu-Ajayi Funmilayo Elizabeth (European Scientific Journal, ESJ, 2017)
The aim of this study is to investigate the effects of mentoring in the utilization and improvisation of Biology learning resources on the performance of senior secondary school students. The main purpose of this study is to mentor the senior secondary students on the utilization of the available Biology learning resources in their schools and the improvisation of unavailable resources, when necessary, for effective learning. The study employed the quasi-experimental design which utilizes non-randomized pretest, post-test, and experimental-control group system. The population of the study was made up of senior secondary school students in South West Nigeria. The sample consisted of 180 Biology students selected from six secondary schools. The sampling technique was multi stage, involving simple random and purposive sampling techniques. The instruments used in the study were Biology learning Resources Questionnaire (BLRQ) and Biology Concept Test (BCT). There was a mentoring package involving a Supplemental Instruction Learning Model. The instrument was validated by experts in science education and test evaluation, and the reliability of the instruments was ascertained using test-retest method. Reliability coefficients of 0.72 and 0.67 were obtained through Pearsons Product Moment correlation statistics. The BCT was administered as both pre-test and posttest, while BLRQ was used to gather information on available learning resources in the secondary schools. In addition, SILM was used for treatment. Data collected were analyzed using Pearsons Product Moment Correlation. It was discovered from the study that mentoring served as an effective tool in encouraging the utilization of available and improvisation of unavailable, but needed, learning resources for Biology teaching and learning in secondary schools. This was discovered to improve students' performance in Biology. Based on the findings of the study, recommendations were made. Among which was that mentoring should be used by Biology teachers as an adjunct to normal classroom teaching, especially in improvisation of learning resources for experiment demonstration during practicals, for effective performance by students.